Terminological Citation Analysis as a Tool for Decision Making and Problem Solving - Chudamani, K. S.; Tejaswini, T. (Journal of Information and Knowledge, 2005)
The paper is base in the analysis of citation drawn from articles published in ’The Indian Journal of Agricultural Sciences’ for the period 2000-2001. It also presents terminological citation analysis for problem solving and decision making processes. The fore steps of decision making enunciated by Carter McNamara have been used.